Acceptability and feasibility of a Japanese version of STrAtegies for RelaTives (START-J): A manualized coping strategy program for family caregivers of relatives living with dementia. (April 2021) - Kashimura, Masami; Rapaport, Penny; Nomura, Toshiaki; Ishiwata, Akiko; Tateno, Amane; Nogami, Akane; Yamashita, Mari; Kawanishi, Tomoya; Kawashima, Yoshitaka; Kitamura, Shin; Livingston, Gill
The rising older population in Japan is associated with a rise in cases of dementia. Support for the increased number of family caregivers of people living with dementia is crucial, as caring may negatively affect a family caregiver's health. This study seeks to evaluate the feasibility and applicability of a recently developed Japanese version of START (STrAtegies for RelaTives). START is a psychosocial coping intervention program developed in the United Kingdom that has been shown to improve caregivers' mood and quality of life in a randomized controlled trial. We made changes to START (e.g., idioms, linguistic nuance, and providing care insurance information suited for Japan) to make it culturally appropriate. Fourteen Japanese female family caregivers of relatives with mild dementia (n = 10) or mild cognitive impairment (n = 4) were referred to the study, but six were excluded owing to illness and busyness. This single-arm study had a before–after trial evaluating psychological outcomes including depression, anxiety, quality of life, and subjective care burden. The acceptance retention and satisfaction rate suggest the feasibility and acceptability of the START program; 8/14 (>55%) eligible, prospective participants consented and were included in this study, all (8/8) of whom completed all START sessions. The mean program satisfaction score was 30.25 (standard deviation = 2.25) out of a potential 32. The results suggest that it is feasible and acceptable to deliver START in Japanese and based on the results of analysis using a linear mixed model, there is initial indication that the intervention improved family caregivers' quality of life, depressive symptoms, and care burden.